Analysis of The Implementation of Early Detection of Growth and Development and Parenting Patterns of Children Aged 0-6 Years - Fitri Ramadhaniati; Deni Maryani; Yetti Purnama; Kurnia Dewiani (Open Access Health Scientific Journal, 2026)
Background: Problems with growth and development disorders continue to increase every year. The low ability of parents to conduct early detection of their child's growth and development results in delayed early interventions that could be carried out. Parenting patterns also determine the appropriateness of a child's growth and development. This study aimed to analyze the implementation of early detection and parenting patterns of children aged 0-6 years.Method: This research is a qualitative study with a descriptive approach. The informants involved in this study numbered 13 people who are mothers of children aged 0-6 years from 10 sub-districts in the city of Bengkulu. The information obtained from the informants includes sources of information, the implementation of early detection, knowledge, and parenting patterns in children. Data were collected through in-depth interviews, document reviews, and observations. The data were analyzed using the narrative analysis method to determine the extent of the implementation of early detection and parental parenting patterns in children aged 0-6 years.Results: Research results show that not all parents obtain information about early detection of child growth and development. Early detection is not conducted continuously according to the child's age stage. Children are generally cared for by their mothers and some of the informants use gadgets in the caregiving process. Children with growth and development disorders are still found.Conclusion: Early detection of child growth and development is still not being implemented, and child care is centered on the mother, with the use of gadgets in the caregiving process. As an effort to optimize child development stimulation, health workers are expected to provide more intensive education to parents, and there is a need for innovative guides for growth and development detection that are easier to use.